2012
DOI: 10.1021/ja303465x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Free Reading of the Histone Code Using a Simple Chemical Sensor Array

Abstract: The histone code refers to the complex network of histone post-translational modifications that control gene expression and are of high interest as drivers of a large number of human diseases. We report here on a mix-and-match toolkit of readily available dyes and calixarene host molecules that can be combined to form dye-displacement sensors that respond to a wide variety of cationic peptides. Using the data from only two or three such simple supramolecular sensors as a chemical sensor array produces fingerpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 61 publications
0
78
0
4
Order By: Relevance
“…31 Please do not adjust margins Please do not adjust margins assays/sensors for antibody free detection of histone modifications through lysine side chain recognition. 35,36 …”
Section: Calixarenesmentioning
confidence: 99%
“…31 Please do not adjust margins Please do not adjust margins assays/sensors for antibody free detection of histone modifications through lysine side chain recognition. 35,36 …”
Section: Calixarenesmentioning
confidence: 99%
“…The underlying idea was that− although ACh and Ch could not be differentiated on account of their identical positive charge and the same NMe 3 + recognition motif, the oxidation product of Ch, betaine, could be detected, because it is zwitterionic, and therefore much more weakly bound ( Figure 5, right). LCG (Figure 2b) was found to be an excellent indicator dye for CX4 (fluorescence enhancement 22 Thus, when the reaction was conducted in the presence of an excess of choline oxidase and a ratedetermining concentration of acetylcholinesterase, the CX4· LCG reporter pair afforded a decrease in fluorescence signal. This resulted from the formation of betaine as weak competitor, which allowed the dye to be taken up by the macrocycle in the course of the reaction.…”
Section: The Quest For Acetylcholine and Choline Sensing Systemsmentioning
confidence: 99%
“…Previous studies have shown that the dye lucigenin is a promiscuous binder of many different sulfonated calixarenes, 39,40 and we found it to be generally well suited to use in a dye-displacement format with each of these compounds. We sought to create a rapid, quantitative assay for H3K27me3 (and H3K27) binding according to the schematic in Fig.…”
Section: Dye Displacement Assay For Histone Tail Bindingmentioning
confidence: 69%